Efficacy and safety of adjuvant radiation therapy in localized adrenocortical carcinoma - Wu, Luming; Chen, Jiayi; Su, Tingwei; Jiang, Lei; Han, Yimin; Zhang, Cui; Zhou, Weiwei; Jiang, Yiran; Zhong, Xu; Wang, Weiqing (Frontiers in Endocrinology, 2024)
Context: Adrenocortical carcinoma (ACC) is a rare malignancy with high rates of recurrence and mortality. The role of adjuvant radiation therapy (RT) in localized ACC was controversial.We conducted a retrospective cohort of ACC patients who were enrolled in our center between 2015 and 2021 to evaluate the efficacy and safety of adjuvant RT in localized ACC. Overall survival (OS) and disease-free survival (DFS) were estimated using the Kaplan-Meier method. Cox proportional hazards regression models were used to estimate the independent risk factors. Adverse events associated with RT were documented according to the toxicity criteria of the radiation therapy oncology group (RTOG) and the common terminology criteria for adverse events (CTCAE v5.0).Of 105 patients with localized ACC, 46 (43.8%) received adjuvant RT after surgery. The median radiation dose was 45.0Gy (range:30.0-50.4) and median follow up time was 36.5 (IQR: 19.7-51.8) months. In comparison to the no adjuvant RT group, patients with adjuvant RT had better 3-year OS (87.9% vs 79.5%, P=0.039), especially for patients with ENSAT Ⅰ/Ⅱ stage (P=0.004). Adjuvant RT also improved the median DFS time from 16.5months (95%CI, 12.0-20.9) to 34.6months (95%CI, 16.1-53.0). Toxicity of RT was generally mild and moderate with six grade 3 events.Postoperative adjuvant RT significantly improved OS and DFS compared with the use of surgery alone in resected ACC patients. Although this retrospective study on RT in localized ACC indicates that RT is effective in ACC, its findings need to be prospectively confirmed.